2017
DOI: 10.1021/acsami.7b14996
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Control as a Powerful Tool for Improving the Selectivity of Antimicrobial Polymers

Abstract: Antimicrobial polymers appear as a promising alternative to tackle the current development of bacterial resistance against conventional antibiotics as they rely on bacterial membrane disruption. This study investigates the effect of segmentation of hydrophobic and cationic functionalities on antimicrobial polymers over their selectivity between bacteria and mammalian cells. Using RAFT technology, statistical, diblock, and highly segmented multiblock copolymers were synthesized in a controlled manner. Polymers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(151 citation statements)
references
References 63 publications
5
144
2
Order By: Relevance
“…Optimizing the conditions for aqueous RAFT polymerization enabled the RAFT terminal to maintain high livingness and the polymers to be prepared in a short period of time. The sequence‐controlled multiblock copolymers by RAFT polymerization were utilized in biological applications, and the influence of the monomer sequence on the function was studied …”
Section: Properties Of Aqueous Raft Polymerization For Preparation Ofmentioning
confidence: 99%
“…Optimizing the conditions for aqueous RAFT polymerization enabled the RAFT terminal to maintain high livingness and the polymers to be prepared in a short period of time. The sequence‐controlled multiblock copolymers by RAFT polymerization were utilized in biological applications, and the influence of the monomer sequence on the function was studied …”
Section: Properties Of Aqueous Raft Polymerization For Preparation Ofmentioning
confidence: 99%
“…Also, in some antimicrobial polymer studies, the self‐assembly of polymers in solution removes the antimicrobial activities . In previous work, less hydrophobic monomers were used allowing block structures to maintain antimicrobial efficacy. This suggests that the type of hydrophobic monomers is an important consideration for antimicrobial polymers with clustered/block formations, especially with highly hydrophobic functional groups such as phenylethyl …”
Section: Figurementioning
confidence: 99%
“…[42][43][44][45][46][47][48][49][50][51][52][53][54][55] Recent studies have reported that polymer structures (i.e., sequences and topology structures) remarkably affect the properties or functions of polymers. 53,[56][57][58][59][60] Thus, the future combination of these modern CRP techniques with the method used herein might offer new polymeric probes for the more rapid, more precise detection of FA in biological systems.…”
Section: Possible Extensions and Challengesmentioning
confidence: 99%